Cases of melioidosis in a university teaching hospital in Malaysia - Raja, N.S. (2008)
Melioidosis is an infectious disease caused by Burkholderia pseudomallei that is endemic in Southeast Asia and northern Australia and has also been reported from non-endemic areas of the world. Little is known about the antimicrobial susceptibility pattern and the demography of melioidosis patients in Malaysia. This was a retrospective study of 83 patients with culture-proven B. pseudomallei infections from the University of Malaya Medical Centre, Kuala Lumpur, Malaysia from May 1995 to June 2005. Antimicrobial susceptibility of B. pseudomallei, age, gender and race of patients, nature of specimen, serological evidence and monthly distribution of cases were evaluated. All isolates were susceptible to piperacillin and piperacillin-tazobactam. The majority of strains were susceptible to imipenem (99%), ceftazidime (94%), amoxicillin-clavulanic acid (95%), ampicillin-sulbactam (94%), tetracycline (89%), chloramphenicol (94%), trimethoprim-sulfamethoxazole (70%), meropenem (88%) and ciprofloxacin (79%). Significant antimicrobial resistance was noted in aminoglycosides and ampicillin. The male-to-female ratio was 3.15:1, and mean age was 43.85 years. The majority of the patients were middle-aged (41-60 years). Malays and Indians made up 39% and 33% of affected patients, while Chinese and others comprised 25% and 3%, respectively. Of 83 patients, 67 were diagnosed by positive blood cultures, and 16 patients were non-bacteremic cases. There were 22 patients in whom B. pseudomallei grew in more than one clinical specimen, and there were 6 polymicrobial cases. Melioidosis is expanding in endemicity around the world. Control of the disease requires close monitoring, improved clinical laboratory standards and aggressive therapy.